2001
DOI: 10.1103/physrevlett.86.6026
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral-Independent Features of Complex Heartbeat Dynamics

Abstract: We test whether the complexity of cardiac interbeat interval time series is simply a consequence of the wide range of scales characterizing human behavior, especially physical activity, by analyzing data taken from healthy adult subjects under three conditions with controls: (i) a "constant routine" protocol where physical activity and postural changes are kept to a minimum, (ii) sympathetic blockade, and (iii) parasympathetic blockade. We find that when fluctuations in physical activity and other behavioral m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(86 citation statements)
references
References 23 publications
3
83
0
Order By: Relevance
“…Characteristic features at a critical point of a second order phase transition are the divergence of the relaxation time with strongly correlated fluctuations and the scale invariance in the statistical properties. Indeed, a healthy human heart rate has been confirmed robustly to show these types of behavior [1,5,7,11,12].Here we seek a phase transition phenomenon in heart rate in order to support the criticality hypothesis more strongly. We provide evidence that a clear transition of heart rate dynamics between distinct, stable ''phases'' can be revealed in heart rate fluctuations in healthy individuals.…”
mentioning
confidence: 85%
“…Characteristic features at a critical point of a second order phase transition are the divergence of the relaxation time with strongly correlated fluctuations and the scale invariance in the statistical properties. Indeed, a healthy human heart rate has been confirmed robustly to show these types of behavior [1,5,7,11,12].Here we seek a phase transition phenomenon in heart rate in order to support the criticality hypothesis more strongly. We provide evidence that a clear transition of heart rate dynamics between distinct, stable ''phases'' can be revealed in heart rate fluctuations in healthy individuals.…”
mentioning
confidence: 85%
“…The correlation between spectral components and scaling factors was weak under uncontrolled conditions [29]. Although the physiologic foundation of the correlation between the anomalies of scaling exponents and the risk of CVDs has not been well established, the scaling properties of HRV series has shown to be dependent on autonomic nervous activities [13] instead of behavior factors [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…Some evidences had demonstrated that modifying the relative importance of sympathetic and parasympathetic nervous systems could lead to changes of the long-range correlations embedded in HRV series [13]. Moreover, scientists found that the long-range correlations by detrended fluctuation analysis of HRV had advantages over the conventional spectral analysis due to its independence of human behavior [13][14][15] and had been also proved to be useful in diagnosis of cardiovascular diseases [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…1,2 The statistical properties of human heartbeat intervals have particularly attracted extensive attentions. [1][2][3][4][5][6][7][8][9][10] The scale-invariant property, long-range correlations, and multifractal features, etc., have been discovered in the human heartbeat rhythm. [4][5][6][7][8][9][10] The purpose of all these studies is double-folded; to uncover the statistical quantities that will identify the mechanisms underlying the complexity in the human heartbeat dynamics, and to provide means of diagnosis and prognosis of heart disease.…”
Section: Network Analysis Of Human Heartbeat Dynamicsmentioning
confidence: 99%